The YOUth cohort study: MRI protocol and test-retest reliability in adults. (October 2020) - Buimer, Elizabeth E.L.; Pas, Pascal; Brouwer, Rachel M.; Froeling, Martijn; Hoogduin, Hans; Leemans, Alexander; Luijten, Peter; van Nierop, Bastiaan J.; Raemaekers, Mathijs; Schnack, Hugo G.; Teeuw, Jalmar; Vink, Matthijs; et al.
Highlights: Test-retest reliability of structural MRI and DWI data was good. Test-retest reliability of resting-state and task-related fMRI was moderate. Overall, global brain measures are more reliable than local brain measures. Abstract: The YOUth cohort study is a unique longitudinal study on brain development in the general population. As part of the YOUth study, 2000 children will be included at 8, 9 or 10 years of age and planned to return every three years during adolescence. Magnetic resonance imaging (MRI) brain scans are collected, including structural T1-weighted imaging, diffusion-weighted imaging (DWI), resting-state functional MRI and task-based functional MRI. Here, we provide a comprehensive report of the MR acquisition in YOUth Child & Adolescent including the test-retest reliability of brain measures derived from each type of scan. To measure test-retest reliability, 17 adults were scanned twice with a week between sessions using the full YOUth MRI protocol. Intraclass correlation coefficients were calculated to quantify reliability. Global brain measures derived from structural T1-weighted and DWI scans were reliable. Resting-state functional connectivity was moderately reliable, as well as functional brain measures for both the inhibition task (stop versus go) and the emotion task (face versus house). Our results complement previous studies by presenting reliability results of regional brain measures collected with different MRI modalities. YOUth facilitates data sharing and aims for reliable and high-quality data. Here we show that using the state-of-the art YOUth MRI protocol brain measures can be estimated reliably.